Consumption of dietary caffeine and coffee in physically active populations: physiological interactions - Tunnicliffe, J. M.; Erdman, K. A.; Reimer, R. A.; Lun, V.; Shearer, J. (Applied Physiology, Nutrition, and Metabolism, 2008)
Caffeine is a proven ergogenic aid, increasing athletic performance, endurance, and mental chronometry at doses as low as 1-3 mg/kg. As coffee is a readily available and commonly ingested form of caffeine, the two are often equated. However, coffee also contains hundreds of other biologically active compounds, many of which are metabolically distinct from caffeine. The purpose of this review was to examine the prevalence of coffee and (or) caffeine consumption among elite Canadian athletes, and to delineate the effects of coffee and caffeine on physical activity, weight maintenance, performance, and metabolism. A total of 270 self-reported 3-day food records were examined for caffeine intake from athletes registered with Canadian Sport Centres in 2005 and 2006. Athletes ranged in age from 16-45 years, and competed in 38 different sports. Results showed that 30% of athletes ingested >1 mg/kg·day from a variety of sources. Average daily intake was 0.85 ± 13 mg/kg. Caffeine intake was not correlated with any 1 sport; the 10 highest caffeine users were athletes from 9 different sports, including skill, endurance, and power sports. No differences were noted for average caffeine ingestion between summer and winter sports. High caffeine intakes corresponded to coffee ingestion, with the 25 highest individual intakes (193-895 mg/day) from coffee drinkers. In summary, it can be concluded that the majority of high-level Canadian athletes consume dietary caffeine primarily in the form of coffee. However, levels consumed are insufficient to elicit performance enhancement. Potential detrimental effects of caffeine consumption on exercise performance include gastric upset, withdrawal, sleep disturbance, and interactions with other dietary supplements.